17?-Estradiol and Vitamin E Modulates Oxidative Stress-Induced Kidney Toxicity in Diabetic Ovariectomized Rat - Ulas, Mustafa; Cay, Mehmet (Humana Press Inc, 2011)
The aim of this study was to investigate the effects of vitamin E (alpha-tocopherol) and 17 beta-estradiol (E-2) supplementation on malondialdehyde (MDA), glutathione (GSH), vitamin A, beta carotene, selenium-dependent glutathione peroxidase (GSH-Px), zinc-dependent superoxide dismutase (SOD), and copper/zinc-dependent catalase (CAT) values in the kidney of ovariectomized (OVX) diabetic rats. Forty-two female rats were randomly divided into seven equal groups as follows: group I, control; group II, OVX; group III, OVX+E-2; group IV, OVX+E-2+alpha-tocopherol; group V, OVX+diabetic; group VI, OVX+diabetic+E-2; and group VII, OVX+diabetic+E-2+alpha-tocopherol. E-2 (40 mu g kg(-1)/day) and alpha-tocopherol (100 mu g kg(-1)/day) were given. Bilateral ovariectomy was performed in all groups except group I. After 4 weeks, antioxidant and MDA levels in the kidney for all groups were analyzed. GSH-Px, CAT, SOD, GSH levels, vitamin A, and beta carotene levels were decreased in OVX group compared to those in the control group but MDA level was elevated via ovariectomy. However, E-2 and E-2+alpha-tocopherol supplementations in OVX group was associated with an increase in the GSH-Px, GSH, CAT and Zn-SOD values, vitamin A, and beta carotene levels but a decrease in MDA levels in kidney. The MDA levels in the kidney of diabetic OVX rats were found higher than those in the control and OVX groups. However, GSH, GSH-Px, CAT, SOD, vitamin A, and beta carotene levels in kidney were lower in OVX diabetic rats. On the other hand, E-2 and E-2+alpha-tocopherol supplementations to OVX diabetic rats have caused an increase in GSH-Px, CAT and SOD, GSH, vitamin A, and beta carotene levels but a decrease in MDA levels. In conclusion, the E-2 and E-2+alpha-tocopherol supplementations to diabetic OVX and OVX rats may strengthen the antioxidant defense system by reducing lipid peroxidation, and therefore they may play a role in preventing renal disorders.
Keywords: Ovariectomy; Alpha-tocopherol; Lipid peroxidation; Kidney; Antioxidant enzymes